Pengaruh Kualitas Pelayanan dan Persepsi Harga Terhadap Kepuasan Konsumen Mcdonald’s di Kota Palembang - W, Willy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the influence of service quality and price perception on customer satisfaction at McDonald's in Palembang City. A quantitative approach was used, with data collected through questionnaires distributed to respondents who have consumed McDonald's products in the city. The results indicate that both service quality and price perception positively affect customer satisfaction. Service quality, including speed, friendliness, and professionalism of employees, plays a crucial role in creating a satisfying customer experience. Additionally, price perception aligned with product and service quality enhances customer satisfaction. This study recommends that McDonald's continue improving its service quality and adopt competitive pricing strategies to strengthen customer loyalty and market competitiveness.